DETERMINAN PENGGUNAAN INFORMASI AKUNTANSI PADA USAHA MIKRO KECIL DAN MENENGAH (UMKM) SE KALIMANTAN SELATAN - Safrida, Lili; Sarwani; Nordiansyah, M. (Universitas Lambung Mangkurat, 2024)
The purpose of this research was to analyze the effect of business scale, business age, education, accounting training, and MSMEs perception about accounting on the use of accounting information in South Kalimantan Province MSMEs. This research used quantitative methos. The population in this research were South Kalimantan Province MSMEs listed on Department of Cooperatives, Micro Enterprises and Manpower of South Kalimantan Province in 2022. The sample method used was convenience sampling. Sample in this research was determined by slovin’s formulas and the total of sample was 86 MSMEs. The source of data used was primary data, data analysis techniques using multiple linear regressian analysis which were processed by SPSS 26 version. Based on the result of this research indicated that accounting training had an effect on the use of accounting information. Meanwhile the business scale, business age, education, and MSMEs perception about accounting had no effect on the use of accounting information.